DAIRY INDUSTRIAL HYGIENE: A REVIEW ON BIOFILM CHALLENGES AND CONTROL - Kabwanga, Ismail T.; Yetişemiyen, Atila; Nankya, Shakira (International Journal of Research -GRANTHAALAYAH, 2018)
The development of biofilms and the microbial biofilm adherence into the production equipment and facilities used in the dairy industry is a critical issue that needs to be addressed. Biofilms lead to the contamination of food by pathogenic and spoilage m/os. The microbes cause both company loses due to unsafe spoilt products, equipment depreciation and death of consumers under severe pathogenic out breaks. Biofilms may also lead to a failure of anti- microbial therapy hence major threats to modern medicine. Biofilm formation however is a dynamic process with different mechanisms involved in the biofilm growth. Raw milk provides an ideal medium for the formation of a biofilm as it contains bacteria and is nutrient-rich. This paper gives highlights regarding microbial sources, challenges, biofilm control strategies that include but not limited to physical, mechanical, enzymatic and chemical methods for the effective control of formation and or eradicate biofilm in the dairy industry.